Availability of Class Management skills for the Fourth- Year students "Class Teacher" from their the Point of View - Yousef, Asef; Hassan, Mazin (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This research aimed to identify the availability of Class Management skills for the Fourth- Year students "Class Teacher" at Damascus and Tishreen Universities. To achieve the research's objectives, the researcher prepared a questionnaire consisted of (42) skill, about the degree of practicing the Fourth- Year Class Management skills. Research sample consisted of (224) "Class Teacher" students at Damascus University and (276) "Class Teacher" students at Tishreen University for the academic year 2016/2017.The present research used the descriptive analytical approach. Validity of the questionnaire was established though a jury of (7) of the teaching staff of Faculty at Education of Damascus and Tishreen Universities. Pilot sample consisted of (30) students "Class Teacher", Reliability was established by Cronbach – Alpha Reliability at least (0.895), and (0.944) at t- Retest. The final results showed that the degree of availability the Fourth- Year Class Management skills were middle rated from the view of "Class Teacher" students at Damascus and Tishreen Universities, In addition to, statistically significant differences he degree of availability the Fourth- Year Class Management skills between two Universities in favor of Tishreen University. Providing teaching and learning requirements to "Class Teacher" students and labs, also practical training equipped with modern scientific tools (computers, light blackboard, video films, micro- teaching classes, teaching and training means).